PENGARUH PENDIDIKAN KESEHATAN CUCI TANGAN TERHADAP PERILAKU CUCI TANGAN DI TK AISYIYAH BUSTANUL ATHFAL BALONGUMBULHARJO CANGKRINGAN SLEMAN YOGYAKARTA - Widuri, Widuri; Darmawan, Tomi (Jurnal Kesehatan Masyarakat, 2016)
Background: Improving the quality of life of children one of which is determined by plantingearly child health behavior. Behavior of school children are very varied. If not recognized early, these health problems will affect the learning achievements and future children. Health behavior is a persons response to stimuli or objects associated with illness and disease, health care systems, food, drinks and the environment. Many children do not wash their hands before eating, so it can result in bacteria that is in the hand will be brought in with the food through the mouth and throat to the digestive tract so that the occurrence of gastrointestinal disease. Objective: Knowing the effect of health education hand washing behavior of hand washing in TK Aisyiyah Bustanul Athfal Balong umbulharjo Cangkringan Sleman Yogyakarta. Research methods: This type of research is one group pretest posttest. Research has been conducted kindergarten Aisyiyah Bustanul Athfal Balong Umbulharjo Cangkringan Sleman Yogyakarta for 2 days commencing on 26 April to 28 April 2014. Results: The results of paired samples correlation calculations indicate that there is significant influence effect of health education hand washing behavior of hand washing with sig. (Tailed) .000 Conclusion: A significant difference between the effect of health education hand washingbehavior of hand washing in TK Aisyiyah Bustanul Athfal Balong Umbulharjo Cangkringan Sleman Yogyakarta. Keywords: Hand washing education, behavior